Polymorphism of the atrial natriuretic peptide hormone and hypertension in residents of Calabar and Uyo, Nigeria (2010)
The natriuretic peptide systems also affect blood pressure through its vasodilatory and natriuretic activities generating interest in its role in the development of hypertension. The polymorphisms of the ANP have been investigated in different populations but similar studies are not documented for Nigerian populations. The study investigate the association of -C664G allele of the ANP gene and hypertension in residents of Calabar and Uyo, Nigeria. The study involved 1308 participant of which 612 were patients and 696 were controls from the population. Allele specific polymerase chain reaction and restriction enzyme digestion was used to genotype the population. The -C664G mutation was not observed in this population. This study adds to the data on the -C664G polymorphism and hypertension in human population.